Transformation of Education at Yusuf Abdussatar Kindergarten in Kediri through Visionary Leadership - Marwanah, Siti; Thohri, Muhammad; Bahtiar, B (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research aims to reveal the impact of educational transformation that occurs at Yusuf Abdussatar Kindergarten in Kediri through visionary leadership policies. The research method used is a case study with a qualitative approach. Data were collected through in-depth interviews, observations, and analysis of related documents. Research respondents include the school principal, teachers, parents of students, and students involved in the educational transformation proces. The research findings show that the visionary leadership policies implemented at Yusuf Abdussatar Kindergarten in Kediri have a significant positive impact on improving the quality of education. The transformation includes the development of innovative curricula, training and professional development for teachers, increased parental involvement in children's education, and the creation of a conducive and inspirational learning environment for students. Visionary leadership also plays a crucial role in directing clear visions, missions, and educational goals, as well as motivating all education stakeholders to collaborate in achieving these goals. The implications of this research findings underscore the importance of visionary leadership in facilitating sustainable and quality education transformation at the primary education level, especially in Kindergartens. This research contributes to understanding effective leadership strategies in the context of early childhood education.